Combination of the ankle-brachial index and percentage of mean arterial pressure to improve diagnostic sensitivity for peripheral artery disease: An observational study. Issue 39 (September 2018) - Lin, Han-Wei; Lee, I-Te
Abstract : Abstract: The ankle-brachial index (ABI) is a noninvasive method for screening for peripheral artery disease (PAD). However, false-negative findings of the ABI may limit its clinical use. The percentage of mean arterial pressure (%MAP) calculated from pulse volume recording has been reported to predict all-cause mortality. We hypothesized that the %MAP would be helpful to screen for PAD in subjects with a normal ABI. We examined whether using a combination of the ABI and %MAP would provide greater diagnostic sensitivity for PAD than using the ABI alone. In this cross-sectional study, we retrospectively reviewed the medical records of patients who had undergone multiple detector computed tomography (MDCT) angiography of the lower extremities following measurement of the ABI with pulse volume recording. PAD was diagnosed based on MDCT angiography. A total of 215 lower extremities of 114 patients were included in our analyses. An optimal cut-off %MAP value of 42.5% was used to diagnose PAD based on MDCT in patients with an ABI > 0.90. Using a combination of an ABI < 0.90 and a %MAP ≥ 42.5% as diagnostic criteria for PAD resulted in better sensitivity (76.9%) than using the ABI alone (56.5% for an ABI < 0.90 and 63.4% for an ABI < 1.00). Using logistic regression analysis, we found that patients having both an ABI < 0.90 and an ABI > 0.90 with a %MAP ≥ 42.5% had a significantly higher risk of PAD than those having an ABI > 0.90 with a %MAP < 42.5% (odds ratio = 7.165, P  = .006; odds ratio = 12.544, P  < .001; respectively). Both the sensitivity and specificity were better when using a combination of an ABI ⩽ 0.90 and a %MAP ≥ 42.5% than when using a low or borderline ABI. The %MAP is helpful for PAD screening in subjects with an ABI > 0.90.